Педагогічна фасилітація - механізм розвитку лідерського потенціалу студентів в умовах технічного університету - Гура, Тетяна Віталіївна (НТУ "ХПІ", 2014)
В статті розглядається поняття "фасилітація" та "педагогічна фасилітація". Наголошено на сучасних вимогах до конкурентоспроможного фахівця технічного університету. Визначено зв’язок фасилітації з лідерськими якостями особистості студента технічного ВНЗ. Висвітлено особливості історії впровадження в педагогічну практику особистісно орієнтованого підходу як механізму педагогічної фасилітації. Зроблено акцент на установки вчителя-фасилітатора, які необхідні для розвитку особистості учня. Зазначено основне завдання викладача-фасилітатора - стимулювання і ініціація осмисленого навчання у студентів. Особливу увагу приділено ролі викладача-фасилітатора для розвитку лідерського потенціалу у студентів у технічному ВНЗ.

In the article the concept of "facilitation" and "teacher facilitation." Emphasized the modern requirements for competitive specialist technical university. The connection facilitation of leadership skills of student technical college. The peculiarities of the history of the introduction of teaching practice personality-oriented approach as a mechanism for facilitating teaching. The accent is made on the teacher fysylitatora settings that are required for the development of the individual student. Shows the main task of the teacher - facilitator - encouraging and initiating meaningful learning in students. The effect of facilitation is considered in the aspect of improvement of individual effectiveness of personality, increase of efficiency of activity of her in a collective. Attention is accented on introduction in the educational-educator process of technical university of ideas of humanistic psychology, that assist forming for the students of independence and responsible freedom at the independent working of material of on-line tutorial.
Educational facilitation - mechanism of development of students' leadership potential in terms of technical university
Keywords: викладач-фасилітатор; особистісно орієнтований підхід; конкурентоспроможний фахівець; facilitation; teacher facilitation; personality-oriented approach; leadership potential